Preparation method and application of oil-containing artificial zeolite sandstone

By preparing oil-containing artificial zeolite sandstone samples, the problem of lack of highly representative unconventional oil and gas sandstone samples in the prior art was solved, and the combined effect of imitating different cements was achieved, and oil-containing artificial zeolite sandstone samples with complex pore structures were prepared. It provides scientific explanation and technical support for the relationship between reservoir crude oil and its interface and its infiltration state.

CN117776663BActive Publication Date: 2025-02-14CHENGDU UNIVERSITY OF TECHNOLOGY +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410001397.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-02
Publication Date
2025-02-14
Estimated Expiration
2044-01-02

AI Technical Summary

Technical Problem

The existing technology lacks standard experimental samples of unconventional oil and gas sandstones with strong representativeness, especially oil-containing zeolite sandstone samples, making it difficult to conduct in-depth research on the impact of differential evolution of cemented minerals in reservoirs on reservoir physical properties.

Method used

Provide a preparation method for oil-containing artificial zeolite sandstone, including the use of alkali exciters to stimulate the mixing of aluminum silicon raw materials with quartz sand, forming a sandstone blank, and after curing crystallization and vacuum-saturated oil treatment, it can prepare different pore structures and chemical compositions. sandstone samples.

Benefits of technology

By adjusting the types, composition and proportion of raw materials, imitating the comprehensive effects of different cements, oil-containing artificial zeolite sandstone samples with complex pore structures can be prepared, which can systematically and scientifically explain the relationship between reservoir crude oil and its interface and its infiltration state. Provide technical and theoretical support for the development of unconventional energy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117776663B_ABST
    Figure CN117776663B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing oil-containing artificial zeolite sandstone, comprising the following steps: using an alkali activator to activate aluminum-silica raw materials with volcanic ash activity; mixing the activated aluminum-silica raw materials with quartz sand and casting them into shape; curing and crystallizing to obtain artificial zeolite sandstone; vacuum saturating the obtained artificial zeolite sandstone with oil, and finally obtaining oil-containing artificial zeolite sandstone. The present invention can imitate the comprehensive effects of various cementing materials such as carbonate minerals, sulfate minerals and aluminosilicate minerals on natural sandstone by adjusting the type, composition and ratio of raw materials, so as to analyze and study the adsorption characteristics of nano-mineral slits / pore structures with different chemical compositions and structures on crude oil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of petroleum exploration and development, and specifically relates to a preparation method and application of oil-containing artificial zeolite sandstone. Background Art

[0002] Sandstone is a sedimentary rock, mainly formed by clay deposition and cementing various sand particles under pressure and temperature. Its cement refers to the chemical precipitate that acts as a bond between rock particles during the diagenesis period. The main cements can be divided into several categories, including silica (quartz, chalcedony, etc.), carbonate minerals (calcite, dolomite, etc.), iron (hematite, limonite, etc.), sulfate minerals (gypsum, anhydrite, etc.), zeolite minerals (analcime, lauzenite, etc.), clay minerals (kaolinite, hydromica, chlorite, feldspar, etc.). Among them, zeolite sandstone is a relatively common sandstone in many areas of my country, such as the Ordos Basin, Yanji Basin, Central Sichuan, and Songliao Basin. The cementation process, compaction, and later dissolution during the diagenesis period have a significant impact on the physical properties of sandstone reservoirs. Therefore, it is of great significance to explore the influence of the properties of aluminosilicate cements in zeolite sandstone on the rock physical properties, which has important scientific value for the inversion of geophysical exploration data of sandstone reservoirs.

[0003] Although there are many studies on artificial sandstone samples, there is still a lack of recognized representative standard experimental samples of unconventional oil and gas sandstones. A large number of literature shows that the technology of artificial sandstone samples is in its early stages, mainly including natural gas hydrate sandstone samples, shale sandstone samples and digital sandstone samples. There are few studies on unconventional cores such as sulfate sandstone samples, zeolite sandstone samples and feldspar sandstone samples, especially the production of oil-bearing sandstone samples. In addition, natural sandstone is generally affected by a combination of multiple cementation effects, so it is difficult to clearly define the impact of a single cementation effect on the physical and chemical properties of the rock.

[0004] Due to the differences in origin and geological conditions, the chemical composition of unconventional oil and gas resources varies greatly. The chromatographic analysis results of crude oil from the inland mountainous areas and coastal continental shelf rock formations in my country show that there are nearly 300 components with a mass fraction greater than 0.02%, and the mass fraction of various hydrocarbon compounds accounts for about 60-80%, containing more normal alkanes and olefins. Cycloalkanes are cyclohexanes with various alkyl groups, and the others are sulfur / nitrogen compounds.

[0005] Scientific understanding of sandstone reservoirs is of great significance to crude oil development. With the development of the oil and gas industry, especially the increasing research on unconventional oil and gas reservoirs, the research and development of related artificial rock sample preparation technology is imminent. Therefore, the present invention proposes a preparation method and application of oil-bearing artificial zeolite sandstone to deeply study the influence of differential evolution of cementing minerals in reservoirs on reservoir properties, and provide technical and theoretical support for the development of unconventional energy. Summary of the invention

[0006] It is a trend in the development of petroleum science and technology to combine artificial sandstone samples with experimental research on natural sandstone cores to solve practical problems in oil and gas exploration. This is because the affinity of crude oil in sandstone reservoirs with various physical and chemical environments plays a decisive role in its enrichment state. In theory, it is generally believed that the infiltration of crude oil in sandstone reservoirs and the chemical composition and microstructure of its interface are closely related. The purpose of the present invention is to provide a preparation method and application of oil-containing artificial zeolite sandstone, aiming to prepare sandstone samples with different pore structures and chemical compositions, and systematically and scientifically explain the relationship between reservoir crude oil and its interface and its infiltration state.

[0007] To achieve the above object, the present invention provides a method for preparing oil-containing artificial zeolite sandstone, which is characterized by comprising the following steps:

[0008] S1. Using an alkali activator to activate the aluminum-siliceous raw material having volcanic ash activity;

[0009] S2. The aluminum-silica raw material after the excitation in step S1 is mixed with quartz sand and then poured into a mold to form a sandstone body;

[0010] S3. The sandstone body obtained in step S2 is cured and crystallized to obtain artificial zeolite sandstone;

[0011] S4. The artificial zeolite sandstone obtained in step S3 is subjected to vacuum oil saturation treatment to obtain oil-containing artificial zeolite sandstone.

[0012] Furthermore, the alkaline activator includes a mixture of one or more of alkali metal hydroxides, carbonates, sulfates, phosphates, fluorides, silicates and aluminosilicates.

[0013] Furthermore, the aluminosilicate raw materials with volcanic ash activity contain active silicon dioxide and aluminum oxide; the aluminosilicate raw materials include fly ash, silica ash, metakaolin, slag, steel slag, rice husk ash, and one or more of kaolin activated by high-temperature calcination, sludge ash, oil shale slag, coal gangue, iron ore and lead-zinc tailings.

[0014] Furthermore, the bulk density of the quartz sand is 1420-1560 kg / m 3 .

[0015] The grading of quartz sand is carried out according to the method in the national standard for building sand GB / T 14684-2017, and is expressed by fineness modulus or bulk density, so as to select sand with appropriate fineness modulus, reasonably grade admixtures of different particle sizes, and mix them into sandstone samples with the porosity required for the experiment. In order to imitate sandstone with nano-scale pore structure and extremely low porosity and permeability, on the basis of adjusting the raw material composition and ratio, the grading of the sand and gravel used can also be optimized based on the closest packing theory, and the compactness of artificial sandstone can be improved by fully vibrating and compacting during pouring. For example, silica fume is not only rich in active silica, but also has a good physical filling effect.

[0016] Furthermore, the curing and crystallization process is: steam curing the sandstone body cast in the mold at 85° C. for 2-3 hours, then demolding, and then wrapping and sealing the demolded sandstone body with a plastic film, and then steam curing for 3 days.

[0017] Furthermore, the curing and crystallization process is as follows: the sandstone body cast in the mold is steam cured at 85° C. for 2 h, then demolded, and then immersed in a room temperature water tank for 28 d.

[0018] Furthermore, the curing and crystallization process is: sealing and curing the sandstone blank cast in the mold with a plastic film, demolding after sealing and curing for 24 hours, and then curing for 28 days at room temperature of 20° C. and relative humidity greater than 90%.

[0019] Curing crystallization refers to the crystallization process in which the aluminosilicate raw materials are stimulated by alkali to form cements that bind the quartz sand together, and then the cements are cured at high temperature with steam, which is conducive to the nucleation and growth of the cements, so as to simulate the structure and type of various cements in natural sandstone. The structure of cements includes but is not limited to amorphous cements (opal, phosphate, iron, aluminosilicate, etc.), cryptocrystalline cements (chalcedony, cryptocrystalline phosphate minerals, etc.), microcrystalline cements (microcrystalline carbonate minerals, etc.), crystalline granular cements (carbonates, silicate minerals, etc.), banded / film-like cements (siliceous, phosphorous, clay minerals, etc.), and regenerated cements (quartz, feldspar or calcite, zeolite, etc.). The types of cementing materials include, but are not limited to, base-type cementing, pore-type cementing, contact-type cementing, embedded-type cementing, intercrystalline cementing, grain-embedded cementing, comb-shaped cementing, film-type cementing, enlarged-type cementing, clot-type cementing, etc., one or two or even multiple types of cementing types coexisting as composite cementing types.

[0020] Furthermore, the process of the vacuum oil saturation treatment is as follows: the artificial zeolite sandstone prepared in step S3 is placed in a vacuum container of 1 to 5 kPa for 3 hours, and then the crude oil mixture is injected to immerse the artificial zeolite sandstone in the vacuum container. After the artificial zeolite sandstone is immersed for 1 to 3 hours, the pressure is restored to normal pressure, and then the immersion is continued for 20 hours to finally obtain the oil-containing artificial zeolite sandstone.

[0021] Further, the crude oil mixture includes one or more of methane, ethane, propane, n-hexane, heptane, n-octane, decane, cyclohexane, methylcyclohexane, ethylcyclohexane, 2-methylhexane, ethylene, propylene, butadiene, benzene, xylene and pentadiene.

[0022] Furthermore, the present invention also provides an application of oil-containing artificial zeolite sandstone. The oil-containing artificial zeolite sandstone prepared by the preparation method of the present invention is used to predict the reservoir parameters and occurrence characteristics of the sandstone.

[0023] The oil-bearing artificial zeolite sandstone prepared by the above preparation method was used as the experimental object. The analysis results of the lithology, physical properties, porosity and other characteristics of the reservoir were analyzed by combining electrochemical impedance spectroscopy, lithofacies analysis and rock electrical tests, capillary pressure tests, mercury injection tests, nuclear magnetic resonance methods and other methods. The influence mechanism of its complex pore structure, cement type and content on its micropore evolution mechanism and macroscopic permeability was revealed, and an electrochemical characterization method describing its micropore transmission process and permeability was proposed. An oil-water permeation transmission model was established, thereby realizing the accurate prediction of the reservoir parameters and occurrence characteristics of sandstone.

[0024] The beneficial effects of the present invention are:

[0025] 1. The present invention can imitate the comprehensive effects of various cementing materials such as carbonate minerals, sulfate minerals and aluminosilicate minerals on natural sandstone by adjusting the type, composition and ratio of raw materials, so as to analyze and study the adsorption characteristics of crude oil by nano-mineral slits / pore structures with different chemical compositions and structures.

[0026] 2. The present invention can adjust the molar ratio of silicon dioxide to aluminum oxide in artificial sandstone by introducing different proportions of silica fume to change the pore structure characteristics of artificial sandstone and the composition and structure of cement. Active silicon dioxide is beneficial to the polycondensation reaction and the formation of aluminosilicate polycondensate cement.

[0027] 3. The present invention can change the lithology of artificial sandstone, mainly including pore structure, porosity, permeability, cementing mineral type and its composition and structure, by adjusting sand grading, activator ratio, curing temperature, pressure and time.

[0028] Other advantages, objectives and features of the present invention will be described in the following description to some extent, and to some extent, will be obvious to those skilled in the art based on the following examination and study, or can be taught from the practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1This is a flow chart of a method for preparing oil-containing artificial zeolite sandstone according to the present invention;

[0030] Figure 2 This is the XRD pattern of the artificial zeolite sandstone prepared in Example 1;

[0031] Figure 3 This is the pore size distribution diagram of the artificial zeolite sandstone prepared in Example 1;

[0032] Figure 4 This is the pore size distribution diagram of the artificial zeolite sandstone prepared in Example 6. DETAILED DESCRIPTION

[0033] In order to make the technical solutions, advantages and purposes of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the described embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of this application.

[0034] like Figure 1 As shown, the present invention provides a method for preparing oil-containing artificial zeolite sandstone, comprising the following steps:

[0035] S1. Using an alkali activator to activate the aluminum-siliceous raw material having volcanic ash activity;

[0036] S2. The aluminum-silica raw material after the excitation in step S1 is mixed with quartz sand and then poured into a mold to form a sandstone body;

[0037] S3. The sandstone body obtained in step S2 is cured and crystallized to obtain artificial zeolite sandstone;

[0038] S4. The artificial zeolite sandstone obtained in step S3 is subjected to vacuum oil saturation treatment to obtain oil-containing artificial zeolite sandstone.

[0039] Example 1

[0040] The process of preparing oil-containing artificial zeolite sandstone in this embodiment is as follows:

[0041] First, 250g of fly ash and 600g of sand (bucket density 1420kg / m 3) is made into a uniform dry mixture, and then 8 mol / L NaOH aqueous solution is prepared, and then 100g NaOH aqueous solution (8 mol / L) is mixed with the dry mixture, and after stirring evenly, the slurry is introduced into a test mold for vibration molding to form a sandstone body; the sandstone body is then placed on a bracket in a constant temperature water tank at 85°C for steam curing for 3 hours, and demolded after curing is completed, and then the test piece is wrapped and sealed with a plastic film, and steam curing is continued for 3 days to finally obtain artificial zeolite sandstone.

[0042] The compressive strength test showed that the compressive strength of the artificial zeolite sandstone prepared in Example 1 was 41.21 MPa. Samples were taken from the debris for compressive strength testing and subjected to XRD and mercury injection testing. Figure 2 As shown, from the XRD phase analysis, it can be seen that the cementing materials of the artificial zeolite sandstone prepared in Example 1 are mainly feldspar and zeolite, and it is a core experimental sample that imitates the natural composite cementing type.

[0043] The porosity of the pores was 13.61% and the average pore size was 175.81 nm after mercury intrusion testing. Figure 3 shown.

[0044] After saturation with water and octane, its oil saturation is 81.23%.

[0045] The test process of saturated water and oil is as follows:

[0046] The first is the vacuum saturation process. The prepared sample (prepared artificial zeolite sandstone) is placed in a low-pressure vacuum container for 3 hours, and then water is injected to immerse the artificial zeolite sandstone sample. After immersion for 1 hour, the sample is restored to normal pressure and then immersed for another 20 hours. After immersion, it is weighed to obtain W1. The artificial zeolite sandstone after immersion is placed in a vacuum oven at 105°C and dried to constant weight to obtain W2. The saturation amount is W1-W2.

[0047] The second is the vacuum oil saturation process. The above vacuum saturated and dried samples are placed in a 5kPa vacuum container, and then 70°C liquid mineral oil is injected to immerse the sandstone samples. After 3 hours, the pressure is restored to normal and then immersed for another 20 hours. After immersion, W3 is weighed and the oil saturation is W3-W2.

[0048] Finally, the oil saturation is

[0049] Example 2

[0050] The process of preparing oil-containing artificial zeolite sandstone in this embodiment is as follows:

[0051] First, 225g of fly ash, 25g of silica ash, and 600g (with a bulk density of 1420kg / m 3) sand is made into a uniform dry mixture, and then a 10 mol / L NaOH aqueous solution is prepared. 100 g of NaOH aqueous solution (10 mol / L) is taken and mixed with the dry mixture. After stirring evenly, the slurry is introduced into a test mold and vibrated to form a sandstone body. The sandstone body is then placed on a bracket in a constant temperature water tank at 85°C and steam cured for 2 h. After the curing is completed, the mold is demolded and the test piece is immersed in a room temperature water tank for 28 d.

[0052] Then, water-saturated, octane-saturated and compressive strength tests were carried out. As in Example 1, the compressive strength of the artificial zeolite sandstone prepared in Example 2 was 31.41 MPa, and the oil saturation was 91.91%.

[0053] Example 3

[0054] The process of preparing oil-containing artificial zeolite sandstone in this embodiment is as follows:

[0055] First, water glass (mass fraction of silicon dioxide is 27.7%, mass fraction of sodium oxide is 7.7%) and a certain amount of NaOH are mixed and stirred until completely dissolved to prepare a water glass solution with a modulus of 2. After standing at room temperature for 24 hours, 144g of water glass solution and 4.6g of sodium sulfate are dissolved in 116g of tap water to obtain an alkali-activated solution; secondly, 240g of slag, 160g of fly ash powder, and 1200g of sand (bucket density is 1560kg / m 3 ) to form a uniform dry mixture, then stir and mix the dry mixture with the prepared alkali-activated solution, introduce the slurry into a test mold and vibrate to form a sandstone body; then wrap the sandstone body with a plastic film, seal and cure for 24 hours, then demould, and continue to cure for 28 days at room temperature of 20°C and relative humidity greater than 90%. The mass of sodium oxide in the alkali-activated solution of this example accounts for 5% of the total mass of slag and fly ash powder.

[0056] Then, the water saturation, octane saturation and compressive strength tests were carried out. The compressive strength of the artificial zeolite sandstone prepared in Example 3 was 39.22MPa and the oil saturation was 83.45% as in Example 1.

[0057] Example 4

[0058] This example is the same as Example 3, but there is one difference, in this example, 3.4g of sodium carbonate is used to replace 4.6g of sodium sulfate in Example 3. Then, saturated water, saturated octane and compressive strength tests are carried out. As in Example 1, the compressive strength of the artificial zeolite sandstone prepared in Example 4 is 61.47MPa, and the oil saturation is 79.23%.

[0059] Example 5

[0060] The process of preparing oil-containing artificial zeolite sandstone in this embodiment is as follows:

[0061] First, 250g of fly ash and 750g of sand (bucket density 1420kg / m 3 ) is made into a uniform dry mixture, and then a 10 mol / L NaOH aqueous solution is prepared, 100 g of the NaOH aqueous solution (10 mol / L) is taken and mixed with the dry mixture, and after stirring evenly, the slurry is introduced into a test mold for vibration molding to form a sandstone body; the sandstone body is then placed on a bracket in a constant temperature water tank at 85°C and steam-cured for 2 hours. After the curing is completed, the mold is removed, and then the test piece is wrapped and sealed with a plastic film, and steam-cured for 3 days is continued to obtain artificial zeolite sandstone.

[0062] Then, water-saturated, octane-saturated and compressive strength tests were carried out. As in Example 1, the compressive strength of the artificial zeolite sandstone prepared in Example 4 was 44.51 MPa, and the oil saturation was 80.56%.

[0063] Example 6

[0064] The process of preparing oil-containing artificial zeolite sandstone in this embodiment is as follows:

[0065] First, 225g of metakaolin, 25g of silica fume, and 600g (bulk density 1420kg / m 3 ) sand is made into a uniform dry mixture, and then a 12 mol / L NaOH aqueous solution is prepared. Then 100 g of the NaOH aqueous solution (12 mol / L) is mixed with the dry mixture. After stirring evenly, the slurry is introduced into a test mold for vibration molding to form a sandstone body. The sandstone body is then placed on a bracket in a constant temperature water tank at 85°C for steam curing for 2 h. After curing, the mold is removed and the specimen is immersed in a room temperature water tank for 28 d to finally obtain artificial zeolite sandstone.

[0066] According to the compressive strength test, the compressive strength of the artificial zeolite sandstone prepared in Example 6 is 61.41 MPa.

[0067] The porosity of the pores was 8.06% and the average pore size was 13.96 nm after mercury intrusion testing. Figure 4 As shown, it can be used as an experimental sample to imitate the nanopore structure of natural sand and stone.

[0068] Oil immersion process and oil saturation test: first take out the curing specimen that has been immersed in the water tank, wipe off the surface moisture and weigh it to obtain W1; place the dried sample (prepared artificial zeolite sandstone) in a vacuum oven at 105°C and dry it to constant weight to obtain W2; then place the sample dried to constant weight in a 5kPa vacuum container, and inject a mixed solution of octane and ethylcyclohexane (volume ratio of 1:1) to immerse the sandstone sample. After 3 hours, restore to normal pressure and then soak for another 20 hours. After soaking, weigh it to obtain W3, and the oil mass is W3-W2.

[0069] Therefore, the oil saturation can be obtained as Oil-bearing artificial zeolite sandstone.

[0070] In addition, many tight natural sandstone reservoirs have the characteristics of low pore size, low permeability, complex pore structure and high bound water saturation. The electrochemical impedance spectroscopy of these characteristic sandstone reservoirs is very different from that of conventional reservoirs, which is not only affected by their complex pore structure, but also by the composition, type and content of the cement. Therefore, for these characteristic sandstones, it is necessary to use artificial sandstone as a sample to conduct in-depth research on the electrochemical impedance spectroscopy of their reservoirs, and combine the analysis of pore structure and cement characteristics to establish a model suitable for the evaluation of oil saturation in tight reservoirs, so as to improve the accuracy of revealing the mechanism of tight sandstone reservoirs.

[0071] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be included in the protection scope of the present invention.

Claims

1. A method for preparing oil-containing artificial zeolite sandstone, characterized in that: The following steps are involved: S1. Using an alkali activator to activate the aluminum-siliceous raw material having volcanic ash activity; The alkaline activator includes a mixture of one or more of alkali metal hydroxides, carbonates, sulfates, phosphates, fluorides, silicates and aluminosilicates; The aluminosilicate raw material with volcanic ash activity contains active silicon dioxide and aluminum oxide; the aluminosilicate raw material includes fly ash, silica ash, metakaolin, slag, steel slag, rice husk ash, and one or more of sludge ash activated by high-temperature calcination, oil shale slag, coal gangue, iron ore and lead-zinc tailings; S2. The aluminum-silica raw material after the excitation in step S1 is mixed with quartz sand and then poured into a mold to form a sandstone body; S3. The sandstone body obtained in step S2 is cured and crystallized to obtain artificial zeolite sandstone; S4. The artificial zeolite sandstone obtained in step S3 is subjected to vacuum oil saturation treatment to obtain an oil-containing artificial zeolite sandstone; The process of the vacuum oil saturation treatment is as follows: the artificial zeolite sandstone prepared in step S3 is placed in a vacuum container of 1-5 kPa for 3 hours, and then the crude oil mixture is injected to immerse the artificial zeolite sandstone in the vacuum container, and the artificial zeolite sandstone is immersed for 1-3 hours to restore to normal pressure, and then continue to immerse for 20 hours, and finally obtain the oil-containing artificial zeolite sandstone; The crude oil mixture includes multiple types of methane, ethane, propane, n-hexane, heptane, n-octane, decane, cyclohexane, methylcyclohexane, ethylcyclohexane, 2-methylhexane, ethylene, propylene, butadiene, benzene, xylene, and pentadiene.

2. The method for preparing oil-containing artificial zeolite sandstone according to claim 1, characterized in that: The bulk density of the quartz sand is 1420-1560 kg / m 3 .

3. The method for preparing oil-containing artificial zeolite sandstone according to claim 1, characterized in that: The curing and crystallization process is as follows: the sandstone body cast in the mold is steam cured at 85° C. for 2-3 hours, then demolded, and then the demolded sandstone body is wrapped and sealed with a plastic film, and then steam cured for 3 days.

4. The method for preparing oil-containing artificial zeolite sandstone according to claim 1, characterized in that: The curing and crystallization process is as follows: the sandstone blank cast in the mold is steam cured at 85° C. for 2 hours, then demolded, and then immersed in a water tank at room temperature for 28 days.

5. An application of an oil-containing artificial zeolite sandstone, wherein the oil-containing artificial zeolite sandstone is manufactured by the preparation method described in any one of claims 1 to 4, and the oil-containing artificial zeolite sandstone is used to predict the reservoir parameters and occurrence characteristics of the sandstone.

Citation Information

Patent Citations

  • Manufacturing method of low-cost sandstone artificial rock core for experimental teaching

    CN105738179A

  • Preparation method of Guantao Formation shallow-stratum loosened oil-containing artificial sandstone core

    CN107144452A